2018
DOI: 10.1172/jci99042
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor polyglutamine expansion drives age-dependent quality control defects and muscle dysfunction

Abstract: Skeletal muscle has emerged as a critical, disease-relevant target tissue in spinal and bulbar muscular atrophy, a degenerative disorder of the neuromuscular system caused by a CAG/polyglutamine (polyQ) expansion in the androgen receptor (AR) gene. Here, we used RNA-sequencing (RNA-Seq) to identify pathways that are disrupted in diseased muscle using AR113Q knockin mice. This analysis unexpectedly identified substantially diminished expression of numerous ubiquitin/proteasome pathway genes in AR113Q muscle, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 76 publications
4
22
0
Order By: Relevance
“…1c, d). These data complement a recent study from our group demonstrating diminished proteasome expression and function in AR113Q muscle and show that SBMA atrophy has several distinctions from other forms of atrophy [53].…”
Section: Ar113q Muscle Atrophy Is Independent Of Ubiquitin-proteasomesupporting
confidence: 90%
See 3 more Smart Citations
“…1c, d). These data complement a recent study from our group demonstrating diminished proteasome expression and function in AR113Q muscle and show that SBMA atrophy has several distinctions from other forms of atrophy [53].…”
Section: Ar113q Muscle Atrophy Is Independent Of Ubiquitin-proteasomesupporting
confidence: 90%
“…Notably, impaired MEF2 activity occurs without concurrent alterations in the activity of the canonical UPS-mediated atrophy pathway (Fig. 1) [53], disruption of signaling pathways that influence muscle hypertrophy (Fig. 2), or significant impairment of the muscle stem cell niche (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings add to the vast body of evidence linking lithium-induced inhibition of GSK3b activity with autophagy induction, showing that besides autophagy, GSK3b inhibition may empower the UPS. This is key since RNA-sequencing studies recently identified the UPS as one of the major pathways being disrupted in the muscle of ARpolyQ-knockin mice [139]. In fact, numerous UPS genes are downregulated in AR113Q-expressing muscle, encoding approximately 30% of UPS subunits and 20% of E2 ubiquitin-conjugating enzymes.…”
Section: Autophagy and The Ups In Sbma Muscle And Axonsmentioning
confidence: 99%